Mucosal melanoma: clinical, histological and c‐kit gene mutational profile of 86 French cases - Cinotti, E.; Chevallier, J.; Labeille, B.; Cambazard, F.; Thomas, L.; Balme, B.; Leccia, M.T.; D'Incan, M.; Vercherin, P.; Douchet, C.; Rubegni, P.; Perrot, J.L. (Journal of the European Academy of Dermatology and Venereology, 2017)
Background Mucosal melanomas are rare and highly aggressive tumours. Few studies evaluated mucosal melanomas of locations other than the head and neck region, and other than those of the Asian population. Objectives The objective of this study was to analyse the clinical and histological features, as well as the mutational status of c‐kit and b‐raf gene of mucosal melanoma in any localization in a French series. Methods We investigated clinical (sex, age, performance status, survival, treatment of the patients and lack of pigmentation of the tumours) and histopathological features (ulceration, Breslow's index, mitotic rate), as well as the mutational status of c‐kit and b‐raf of 86 mucosal melanomas diagnosed in 15 years in four French University Hospitals. Results Most melanomas affected women (72%) and the genital region (46.5%). A fifth of melanomas were amelanotic. 81% of melanomas had a Breslow's index ≥1, whereas all glans melanomas, and most vulvar melanomas had a Breslow index ≤1 mm. Overall survival was 54% at 3 years; 11.6% of the 43 tested mucosal melanomas were c‐kit‐mutated while the 15 tested genital melanomas were not. The c‐kit gene mutation did not influence the overall survival. Age ≥ 50, amelanotic type and performance status ≥1 were not poor prognostic factors in our series. Conclusion This study confirmed that mucosal melanomas are rare and could be difficult to diagnose being often amelanotic and in hidden sites. Most melanomas were thick at the diagnosis, but glans and vulvar melanomas were thinner probably because of their greater visibility. The frequency of the c‐kit mutation varied depending on the initial tumour site. In our series, the prognosis was poor, independently from c‐kit mutations and the patient's general health and age. The presence of metastasis at diagnosis was associated with a worse prognosis indicating the importance of an early diagnosis.